Formulation and development of bilayer tablet containing irbesartan and metformin hydrochloride for diabetic hypertensive patients - Gorde, V D; Rachh, Punit R; Mankar, Someshwar; Amin, Saurin; Gorde, Prasad L (Creative Pharma Assent, 2024)
Background: Hypertension is a common complication of type II diabetes. The present research work aimed to develop bilayer tablets that would manage type II diabetes patients with hypertension. The prepared bilayer tablet has an immediate-release layer of anti-hypertensive irbesartan and a sustained-release (SR) layer of anti-diabetic metformin hydrochloride. The purpose of these bilayer tablets was to increase patient compliance by converting two separate monotherapy to single combination therapy. Methodology: Several ratios of polymers, including HPMC K100M, EC, Eudragit, and Guar gum, were employed to prolong the drug release for twelve hours. An immediate-release layer of irbesartan was prepared by spherical agglomeration. The physical properties, drug content, solubility profiles, release kinetics, and stability of prepared bilayer tablets were assessed. Results and Discussion: The examination of SR granules and bilayer tablets revealed outstanding packing qualities and excellent flow properties, with bulk and tapped densities ranging from 0.39-0.46 g/cm³ and 0.42-0.55 g/cm³, respectively. In vitro dissolution tests revealed that the immediate-release layer gave an initial burst of Irbesartan. Still, the sustained-release layer of metformin showed controlled drug release over 12 hours at greater polymer concentrations. According to stability testing, the bilayer tablets' physical properties, drug content, and dissolving profiles did not change significantly. Conclusion: The bilayer tablet combination of Irbesartan and Metformin exhibited desired physical features, controlled drug release, and stability. This formulation represents a viable treatment option for diabetic hypertensive patients, offering effective and consistent management of both disorders while improving patient compliance.